Routledge international handbook of sex industry research / edited by Susan Dewey, Isabel Crowhurst, and Chimaraoke Izugbara. - Dewey, Susan; Crowhurst, Isabel; Izugbara, Chimaraoke O. (Routledge international handbooks., 2019)
The Routledge International Handbook of Sex Industry Research unites 45 contributions from researchers, sex workers, activists, and practitioners who live and work in 28 countries throughout the world. Focusing tightly on the contemporary state of sex industry research through eight carefully selected themes, this volume sets a clear agenda for future research, activism, and policymaking.